Dakwah di Tengah Heterogenitas Masyarakat dan Perbedaan Umat - Ningsih, Yusria; Aflika, Ulul (Proceedings of International Conference on Da'wa and Communication, 2019)
Pluralism of the old term is increasingly getting the full attention of many circles. The term is not new, because the discussion regarding plurality itself has been further elaborated by transcendental Greek thinkers with various alternative solutions. Plurality is identified variously by these thinkers attached to various solution solutions for plurality. Is a given pluralism, while conflict is inhern. Next what comes to mind is how to manage plurality and conflict can become social energy in realizing a harmonious and better national order. The answer is brief regarding the assessment of many factors. In considering plurality, agreeing that harmony is not enough if only carried out apathetically and passively. It is also expected that pluralist self-attitudes also measure pluralism. Respect and acknowledge the existence of others, place according to foster an attitude of empathy, honesty, and fairness. So by using the collaboration of all parties, both different Islam and outside Islam, also using the assets of the world which will make the plural model of Islamic propaganda more useful. Thus, plurality, heterogeneity, diversity or diversity can become "social energy" in controlling and neutralizing human problems.